2021
DOI: 10.1055/s-0041-1724024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Plasma Soluble Triggering Receptor Expressed on Myeloid Cells-1 in Children with Urinary Tract Infections

Abstract: Objective The aim of the present study was to evaluate the diagnostic value of soluble triggering receptor on myeloid cells-1 as a novel marker for diagnosis of childhood urinary tract infections (UTI). Methods This study enrolled 30 pediatric patients diagnosed with acute febrile UTIs; 30 healthy children were included as the control group. The blood samples from the patients and healthy controls were collected for a soluble triggering receptor on myeloid cells-1 (sTREM-1) test. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was previously demonstrated that in pediatric patients diagnosed with acute febrile UTIs, plasma sTREM-1 levels were higher compared to healthy controls. Additionally, it was reported that sTREM-1 exhibited diagnostic performance with a sensitivity of 57% and a specificity of 50% [25]. In a study conducted by Sierra-Diaz et al, differences in TREM-1 expression in children with and without UTIs were investigated through flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that in pediatric patients diagnosed with acute febrile UTIs, plasma sTREM-1 levels were higher compared to healthy controls. Additionally, it was reported that sTREM-1 exhibited diagnostic performance with a sensitivity of 57% and a specificity of 50% [25]. In a study conducted by Sierra-Diaz et al, differences in TREM-1 expression in children with and without UTIs were investigated through flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…44 In a recent comparative study, 30 children with culture-positive febrile UTI and 30 healthy controls were investigated for the diagnostic value of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) as a novel biomarker for childhood UTI. 45 sTREM-1 had a sensitivity of 57% and a specificity of 50% for the diagnosis of UTI. TREM-1 is a protein surface receptor that amplifies toll-like receptorinduced inflammation by increased production of proinflammatory cytokines.…”
Section: More Recent Novel Biomarkers In Urinary Tract Infection Diag...mentioning
confidence: 97%
“…At present, many reports have shown that amoxicillin and clavulanate potassium can reduce the clinical symptoms of UTI children, and especially oral administration of this drug can reduce the incidence of complications such as phlebitis, with definite efficacy [ 6 , 7 ]. However, UTI can recur in children due to factors such as immunocompromise, and recurrence is an important reason for the development of UTI into chronic renal failure [ 8 , 9 ]. However, amoxicillin and clavulanate potassium cannot improve the immune function of children, so it is extremely important to combine it with other therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%